Anterior Open-Wedge Osteotomy to Correct Sagittal and Coronal Malalignment in a Case of Failed High Tibial Osteotomy and Failed Posterior Cruciate Ligament Reconstruction - K. Raghuveer Reddy, M.S., D.N.B.; N. Somasekhara Reddy, M.S., M.Ch.; N. Prakash, M.S. (Arthroscopy Techniques, 2024)
Anterior open-wedge high tibial osteotomy of the proximal tibia is a reliable surgical procedure to treat genu recurvatum secondary to decreased posterior tibial slope. It is also useful in cases of posterior cruciate ligament (PCL) deficiency, especially after a failed PCL reconstruction procedure as reversal of posterior tibial slope is a common risk factor for failure of PCL reconstruction. In some knee joints, reversed tibial slope may be associated with varus or valgus deformity. We describe correction of reverse posterior slope along with varus deformity, which may result from a poorly performed high tibial osteotomy leading to failure of reconstructed PCL. In our technique, both of the above deformities are corrected simultaneously, thereby addressing the sagittal and coronal malalignments of the knee with one osteotomy.